Integration Life Skills Education In History Learning With Online Learning On The Covid-19 Pandemic (Case Study in SMA N 1 Boyolali) - Muadz Assidiqi; Sariyatun Sariyatun; Hieronymus Purwanta (International Journal of Science and Applied Science: Conference Series, 2021)
Anderson and Krathwohl's overly rigid use of educational taxonomy led to life skills education having no clear fundamentals. This research aims to illustrate the integration of life skills in soft skills in historical learning during the Covid-19 pandemic at SMAN 1 Boyolali High School with a taxonomy of life skills education. This research is descriptive qualitative research with a case study approach. The data source in this study is obtained through interviews, observations, and documentation narrated into a sentence. Furthermore, the data source is analyzed interactively through data condensation, presentation, and conclusions. The results of this study are a detailed depiction of indicators of life skills education integrated by history teachers to improve students' soft skills. The newness in this study is the use of taxonomy of life skills education that is still not widely known by teachers and educational academics.